2013
DOI: 10.4021/wjon627w
|View full text |Cite
|
Sign up to set email alerts
|

Rectal Plasmablastic Lymphoma in HIV/AIDS: Two Cases

Abstract: Plasmablastic lymphoma is an aggressive variant of large B-cells lymphoma in which the infection by Human Immunodeficiency Virus and Epstein-Barr herpesvirus are involved. This recently denominated neoplasia has a special tropism through the oral cavity. However, its presence has been reported in the digestive tract, abdominal cavity and retroperitoneum. We describe two Human Immunodeficiency Virus infected patient cases with rectal presentation of PL in the HIV service of the Hospital Civil de Guadalajara.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Isolated cases of plasmablastic lymphoma have been reported in the rectum with a presentation similar to that of the case presented, such as a rectal mass with signs of local inflammation. The mass tends to be painful on palpation, friable to the touch and protrudes through the anal canal with local invasion of surrounding tissues, which can be accompanied by rectal bleeding and pain on defecation [5][6][7][8]. Only scarce cases of plasmablastic lymphoma of the rectum have been reported in HIVnegative patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Isolated cases of plasmablastic lymphoma have been reported in the rectum with a presentation similar to that of the case presented, such as a rectal mass with signs of local inflammation. The mass tends to be painful on palpation, friable to the touch and protrudes through the anal canal with local invasion of surrounding tissues, which can be accompanied by rectal bleeding and pain on defecation [5][6][7][8]. Only scarce cases of plasmablastic lymphoma of the rectum have been reported in HIVnegative patients.…”
Section: Discussionmentioning
confidence: 99%
“…This was first described in 1997 in the oral cavity of patients with human immunodeficiency virus (HIV) infection. This began being considered an acquired immunodeficiency syndrome (AIDS)-defining neoplasm [1][2][3][4][5]. This represents approximately 2% of HIV-related lymphomas and less than 3% of all non-Hodgkin lymphomas [1,4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taking into account the recommendations issued by The International Lymphoma Radiation Oncology Group (ILROG) for the treatment of hematological neoplasms during the COVID-19 pandemic, we are in the palliative field of a patient with an aggressive, symptomatic non-Hodgkin's lymphoma, so a hypofractionated scheme of 25 Gy in 5 Fractions was chosen, with an EQD2 for an α/β of 3 Gy = 40 Gy and an α/β of 10 Gy = 31 Gy, with the expectation of an equivalent biological effect that it would maintain the same level of tumor control, with a low risk of early and late toxicity in healthy tissues, given current radiotherapy techniques and the prescribed dose. [1][2][3][4][5][6][7][8][9][10][11][12][13]…”
Section: Discussionmentioning
confidence: 99%
“…However, upon review, in fact, we found it to be the most common site for EoPL, with a total of 12 cases being identified from the available literature [6,16,17,20,21,22,23]. The other common sites include the stomach, skin, cervical lymph node and orbit, with a similar incidence [10,11,15,17,24,25,26,27,28,29,30,31,32,33,34].…”
Section: Discussion and Review Of The Literaturementioning
confidence: 99%